Perceptions of Undergraduate Medical Students on Quiz-based Formative Assessment with Immediate Feedback in Integrated Clinical Biochemistry Teaching-learning sessions: Quiz Feedback in Biochemistry Sessions - Mansoor, Sumreena; Javed, Ayesha; Gul, Sawaira; Rashid, Sajid (Pakistan Journal of Health Sciences, 2024)
Historically, medical education has used quizzes to provide knowledge assessments and feedback. This study investigates the impact of a quiz-based formative assessment with instantaneous feedback on the learning experiences of medical students, specifically focusing on retention, comprehension, and engagement. Objective: To examine the impact of quizzes on medical students’ comprehension of material, focusing on their perception of the effectiveness of a questionnaire-based pre and post-quiz evaluation approach and its effects on psychological factors like motivation, self-confidence, critical thinking, and receptive capacity. Methods: Quantitative data were collected from 100 second-year MBBS students through a cross-sectional survey. Expert input and suggested modifications were implemented in conjunction with a modified validated questionnaire. Data were analyzed using descriptive statistics, with frequencies and percentages reported. Results: The study indicated that approximately 63.2% of students felt quizzes helped them focus on relevant material and save study time. Additionally, approximately 55% found quizzes beneficial for understanding metabolic processes in clinical contexts, while approximately 54% reported that quizzes encouraged deeper research and increased engagement. However, some students raised concerns about anxiety and time pressures. Conclusion: Overall, formative evaluation via quizzes enhances students' engagement and comprehension and can be optimized based on feedback to improve medical education.